Theory of Justice’s Principles For A Just and Equitable Global Order - Theofransus Litaay (Dinasti Research, 2025)
This article is part of a literature research in the field of international legal philosophy, which aims to discuss the application of John Rawls' thought in the context of international law. The presentation begins by describing the meaning of justice as a moral and ethical concept according to philosophers and John Rawls' position in it. The discussion is carried out on Rawls's ‘A Theory of Justice’, followed by ‘The Law of Peoples’ and its relation to international law. The essence of this article is to discuss justice (in Rawls' perspective) as a key principle in international law to create a just global order. The author explores Rawls' views on justice, peace, and governance. Rawls' theory of justice as fairness provides a valuable lens to analyse global issues. Rawls argues that just institutions should be based on principles that promote peace, stability, and the well-being of all nations. By adhering to these principles, international law can promote a more just and equitable global order.